A New Mechanical Analysis of a Crankshaft-connecting Rod Dynamics Using Lagrange’s Trigonometric Identities - Hasan H. Ali; Firas M. Abdulsattar; Ahmed W. Mustafa (Institute for Research and Community Services, Institut Teknologi Bandung, 2022)
The main objective of this study was to conduct a new and simple but accurate analysis of the dynamics of a crankshaft-connecting rod system based on Lagrange’s trigonometric identities. Actual and equivalent connecting rod mass approximations of single- and multi-cylinder reciprocating engines were studied. Several examples were studied to demonstrate the dynamics of the system. Lagrange’s trigonometric identities were used to simplify the model, while MATLAB was used to obtain the results. For both the proposed reduced model and the full model, the resultant forces and torques of an actual and an equivalent connecting rod mass were compared. The results showed that the proposed reduced model gives force and torque results that match the results of the full model very well. It was shown that the largest torque imbalance resultant on the crankshaft was exerted by the two-cylinder engine. In addition, it was shown that the largest external forces resultant acting in the x-direction was exerted by the one-cylinder engine. The results also revealed that the resultant of external forces acting in the y-direction was zero for multi-cylinder engines. The relative error, which mainly occurred at the points of maximum force and torque, ranged from about 1% to about 15%.